Dynamic structural colour using vanadium dioxide thin films. (30th May 2018) - Wilson, K; Marocico, C A; Bradley, A L
Abstract: A thin film stack consisting of layers of indium tin oxide (ITO) with an intermediate vanadium oxide (VO2 ) layer on an optically thick silver film has been investigated for dynamic structural colour. The structure benefits from the phase change properties of VO2 . Compared with other phase change materials, such as germanium antimony telluride (GST), VO2 can be offered as a lower power consumption alternative. It has been overlooked in the visible spectral range due to its smaller refractive index change below 700 nm. We demonstrate that the sensitivity of the visible reflectance spectrum to the change in phase of a 30 nm VO2 layer is increased after it is incorporated in a thin film stack, with performance comparable to other phase change materials. The extent to which dynamic tuning of the reflectance spectra of ITO–VO2 –ITO–Ag thin film stacks can be exploited for colour switching is reported, with approximately 25% change in reflectance demonstrated at 550 nm. Inclusion of a top ITO layer is also shown to improve the chromaticity change on phase transition.